Impact of Education Status, Religious Knowledge and Family Economy on the Practicing Prayer Students for Primary School in Setiu District, Terengganu Malaysia - Zamri Chik; Abdul Hakim Abdullah (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2019)
Prayer is a religious pillar where prayer is the greatest of worship that brings the servant closer to his Lord and it is the steadfastness of the relationship of the creature and its creator. The sholat according to syarak is defined as a few words and deeds commenced with takbir and endorsed with greetings and with the conditions specified. This study was conducted to determine the effectiveness of educational status, religious knowledge and family economy on student prayer practice primary school in Setiu District. Total sample 175 secondary school students (level two) of the study. Data were analyzed using IBM-SPSS-AMOS (SEM) program version 21.0. The findings indicate that the educational status, religious knowledge, and family economy on student prayer practice primary school. Furthermore, Inference analysis findings also show educational status, religious knowledge and family economy, have a positive and significant influence on student prayer practice. This shows that family education, especially in religious knowledge and economic family, plays a role in the practice of prayer in primary schools. In conclusion, the implications of this research, the researchers are aware of the need for cooperation from the school to emphasize the students on the practice of prayer in their daily lives. Although the level of education and family economics is a factor in the practice of prayer in this study, the role of teachers helps to overcome them. DOI: https://doi.org/10.5281/zenodo.3467647